2020
DOI: 10.21608/ebwhj.2020.29798.1096
|View full text |Cite
|
Sign up to set email alerts
|

Carbetocin versus Misoprostol in Reducing Blood Loss during Cesarean Section in low risk patients. A Randomized Controlled Trial

Abstract: Aim: This study aimed to compare the use of misoprostol to carbetocin in reducing blood loss during cesarean section in low risk patients. Materials and Methods: This randomized controlled study enrolled 300 patients who were eligible. 150 women received carbetocin100ug i.v intra-operative immediately after extraction of the fetus during cesarean section (group A). They were compared to 150 women who received misoprostol 600ug rectally immediately before sterilization during caesarean section (group B). Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 13 publications
2
9
0
Order By: Relevance
“…We found that carbetocin is superior to misoprostol in reducing blood loss in CS in primigravida. In agreement with our study, Moustafa et al [17] concluded that intravenous therapy infusion of 100 ug carbetocin is more effective in managing blood loss during CS than 600ug rectal misoprostol.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We found that carbetocin is superior to misoprostol in reducing blood loss in CS in primigravida. In agreement with our study, Moustafa et al [17] concluded that intravenous therapy infusion of 100 ug carbetocin is more effective in managing blood loss during CS than 600ug rectal misoprostol.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, the need for blood transfusion was significantly lower in the carbetocin group. This was in agreement with Ali et al [25] and Moustafa et al [17] who found that carbetocin decreases the need for blood transfusion after cesarean.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Although the length and trial settings varied, all included RCTs were conducted in Egypt. Most RCTs [ 14 , 21 , 23 ] used misoprostol per rectum except one [ 22 ], which used it sublingually. Also, three RCTs [ 14 , 21 , 22 ] operated on patients under spinal anesthesia, and one RCT [ 23 ] performed on their patients under general anesthesia.…”
Section: Reviewmentioning
confidence: 99%
“…Most RCTs [ 14 , 21 , 23 ] used misoprostol per rectum except one [ 22 ], which used it sublingually. Also, three RCTs [ 14 , 21 , 22 ] operated on patients under spinal anesthesia, and one RCT [ 23 ] performed on their patients under general anesthesia. Table 1 and Table 2 depict a summarization of the baseline features of the eligible articles.…”
Section: Reviewmentioning
confidence: 99%